Analisis Kelayakan Usahatani Exotic Fish Indonesia - Nisa Hafi Idhoh Fitriana (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2023)
ABSTRACTFarming feasibility is an effort to determine the feasibility level of a business seen from certain parameters or eligibility criteria. Farming can be said to be feasible if it is able to provide benefits to farmers and farmers obtain income that can cover all costs incurred for procuring factors of production. The focus of this research is to analyze ornamental fish farming in the